Reassimilation of Photorespiratory Ammonium in Lotus japonicus Plants Deficient in Plastidic Glutamine Synthetase - Pérez-Delgado, Carmen M. (PLoS One, 2015)
It is well established that the plastidic isoform of glutamine synthetase (GS(2)) is the enzyme in charge of photorespiratory ammonium reassimilation in plants. The metabolic events associated to photorespiratory NH(4) (+) accumulation were analyzed in a Lotus japonicus photorespiratory mutant lacking GS(2). The mutant plants accumulated high levels of NH(4) (+) when photorespiration was active, followed by a sudden drop in the levels of this compound. In this paper it was examined the possible existence of enzymatic pathways alternative to GS(2) that could account for this decline in the photorespiratory ammonium. Induction of genes encoding for cytosolic glutamine synthetase (GS(1)), glutamate dehydrogenase (GDH) and asparagine synthetase (ASN) was observed in the mutant in correspondence with the diminishment of NH(4) (+). Measurements of gene expression, polypeptide levels, enzyme activity and metabolite levels were carried out in leaf samples from WT and mutant plants after different periods of time under active photorespiratory conditions. In the case of asparagine synthetase it was not possible to determine enzyme activity and polypeptide content; however, an increased asparagine content in parallel with the induction of ASN gene expression was detected in the mutant plants. This increase in asparagine levels took place concomitantly with an increase in glutamine due to the induction of cytosolic GS(1) in the mutant, thus revealing a major role of cytosolic GS(1) in the reassimilation and detoxification of photorespiratory NH(4) (+) when the plastidic GS(2) isoform is lacking. Moreover, a diminishment in glutamate levels was observed, that may be explained by the induction of NAD(H)-dependent GDH activity.